2019
DOI: 10.1007/s11065-019-09412-9
|View full text |Cite
|
Sign up to set email alerts
|

Montreal Cognitive Assessment (MoCA) for HIV-Associated Neurocognitive Disorders

Abstract: This study aims to systematically review the evidence on the accuracy of the Montreal Cognitive Assessment (MoCA) test for diagnosing HIV-associated neurocognitive disorders (HAND) and to outline the quality and quantity of research evidence available about the accuracy of MoCA in populations infected with HIV. We conducted a systematic literature review, searching five databases from inception until January 2019. We extracted dichotomized positive and negative test results at various thresholds and calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 81 publications
0
55
0
Order By: Relevance
“…Having a common and thoughtful diagnostic gold standard would subsequently help at identifying the most suitable screening tools. In this regard, specific techniques of brain magnetic resonance imaging, such as structural MRI and spectroscopy, will potentially help to better detect HAND, giving objective and quantifiable measures of brain involvement [89], since cerebrospinal fluid biomarkers have not proved to be reliable tools and noninvasive procedures should be preferred. Cerebrospinal fluid levels of Neurofilament Light Protein (NFL) and potentially serum levels, if clinically validated, may provide additional information in the setting of central nervous system and neuronal damage and for diagnosing symptomatic HAND [90].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Having a common and thoughtful diagnostic gold standard would subsequently help at identifying the most suitable screening tools. In this regard, specific techniques of brain magnetic resonance imaging, such as structural MRI and spectroscopy, will potentially help to better detect HAND, giving objective and quantifiable measures of brain involvement [89], since cerebrospinal fluid biomarkers have not proved to be reliable tools and noninvasive procedures should be preferred. Cerebrospinal fluid levels of Neurofilament Light Protein (NFL) and potentially serum levels, if clinically validated, may provide additional information in the setting of central nervous system and neuronal damage and for diagnosing symptomatic HAND [90].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…At present, this threshold is widely used for detecting cognitive impairment. However, recent systematic reviews investigating its use in patients with different types of cognitive disorders have revealed that lowering the threshold offers a better balance between true positive and false positive results [ 32 , 33 , 34 , 35 , 36 ]. In order to minimize practice effects, alternative versions of the MoCA have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review evaluating eight studies reported an overall sensitivity of MoCA of 0.73, with a specificity of 0.54 using the same cut-off. When a lower threshold score of 23 balancing true and false-positive results was used, the sensitivity and specificity were 44% and 79%, respectively [21]. Despite a moderate sensitivity and diagnostic accuracy, MoCA has been used in many clinics because of the lack of easy-to-use and free alternatives.…”
Section: Discussionmentioning
confidence: 99%